Pengaruh Kualifikasi Pendidikan, Pengalaman Kerja dan Disiplin Kerja Terhadap Kinerja Guru Di SMA Frater Makassar - Basri Bado; Revoluance Adimuntja (Universitas Negeri Makassar, 2021)
This research is a type of quantitative research that aims to determine and analyze how educational qualifications, work experience and work discipline influence the performance of teachers at Frater Makassar Senior High School. The independent variables in this study are educational qualifications, work experience and work discipline while the dependent variable is teacher performance. The population in this study were all teachers of SMA Frater Makassar consisting of ASN status teachers, permanent foundation teachers, contract teachers, and apprentice teachers as many as 41 teachers, while the sample used saturated sample techniques, namely the entire population was used as the research sample. Research data obtained by using a questionnaire, observation and documentation. The data analysis method used was validity test, reliability test and spearman rank correlation test. The data analysis techniques used were descriptive analysis (average score, standard deviation, variance and percentage), classical assumption test (normality test, linearity test, multicollinearity test, heteroscedasticity test) multiple regression test, t-test, f-test and determination coefficient delta test (ΔR2). The results showed that educational qualifications, work experience and work discipline simultaneously affect teacher performance, the amount of influence given is 24.2%, while the remaining 75.8% is explained or influenced by other variables not selected in this study.